An Analysis of Simple Past Tense Errors in Grade X Students’ Recount Texts - Auliatul Fitri; Piyanart Akkhakraisi; Naveed Ahmad Qaderi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify and analyze the types of grammatical errors made by tenth-grade students in writing recount texts, particularly in the use of the simple past tense, using Surface Strategy Taxonomy and Linguistic Category Taxonomy to reveal patterns of learners’ grammatical difficulties. Methodology: This research employed a descriptive error analysis approach, combining qualitative interpretation with quantitative frequency analysis. The data consisted of recount texts written by tenth-grade students of Senior high school 1 Sumberejo Tanggamus, collected through documentation. The errors were identified, classified, and analyzed based on Surface Strategy Taxonomy and Linguistic Category Taxonomy, with percentages used to indicate error tendencies rather than statistical generalization. Main Findings: The results show that misformation errors were the most dominant type (57.3%), followed by omission (24.3%), addition (5.6%), and misordering (2.8%). Most errors occurred in morphological and syntactic categories, particularly in verb forms related to the simple past tense. These findings indicate that students’ difficulties stem from incomplete mastery of grammatical rules and verb inflections rather than careless mistakes. Novelty/Originality of this study: This study contributes a dual-taxonomy error analysis that integrates Surface Strategy and Linguistic Category approaches to provide a more comprehensive diagnosis of students’ grammatical errors. The findings offer specific pedagogical implications, including the need for targeted grammar instruction, focused practice on verb-form accuracy, and error-based corrective feedback in teaching recount text writing.